Endobridging of Iliac Artery Avulsion Complicating Endovascular Aortic Aneurysm Repair. (2015) - Pinho-Gomes, A.-C.; Goatman, C.; Byott, S.; Seriki, D.; Ghosh, J.
Abstract : Introduction: Iliac avulsion is a potentially catastrophic complication of endovascular procedures, which requires immediate recognition and repair. This study describes an innovative approach to manage this serious complication. Report: An 81-year-old male presenting with a 113-mm infra-renal abdominal aortic aneurysm and bilateral iliofemoral atherosclerosis, including a complete left-sided occlusion, was referred for urgent endovascular aneurysm repair. Repair was approached using an aorto-uniliac endograft deployed through a right iliofemoral bypass conduit. The procedure was complicated by complete avulsion of the common iliac artery close to its origin. Haemostatic control was achieved by deploying an endo-balloon initially over the femoral wire, which was subsequently exchanged with an occlusion balloon from a brachial access point. A bridging iliac limb endograft was deployed across the defect and anchored to the native common iliac artery proximally and distally by interrupted sutures. The remainder of the procedure was completed as planned. Discussion: This case highlights a successful endovascular strategy to control a potentially lethal haemorrhage. Highlights: Iliac artery avulsion is a rare but potentially catastrophic complication of endovascular aneurysm repair, which requires prompt management. Endovascular repair is feasible and avoids the physiological insult associated with conversion to open aneurysm repair. Critical steps: wire stabilisation; ipsilateral balloon control; exchange to second occlusion balloon via contralateral or upper limb access; bridge defect with stent securing proximally and distally.